Experimental Investigations of Ni Nanoparticle-Polyurethane Acrylic Composite for Electrical Conductivity Enhancement. (2019) - Goodwin, Adrian; Kelkar, Ajit D.; Mohan, Ram V.
ABSTRACT: Conductive composites are being considered for use in applications such as electromagnetic shielding. Prior work has shown correlation of electrical conductivity to the microstructure of corresponding composite. In the present paper, composites consisting of polyurethane acrylic and dispersed nickel nanoparticles were fabricated, and tested for their electrical conductivity. In the fabrication process, half of the suspensions were agitated by sonication and half were not. Correlations between electrical conductivity and composite microstructural details are presented. These correlations show an optimum concentration of nickel nanoparticles that result in maximum conductivity enhancement. In addition, sonicating the suspensions increased conductivity of resulting nanocomposites. Scanning Electron Microscopy (SEM), Energy Dispersive Spectroscopy (EDS) images were used to estimate surface concentration and distribution of Nickel nanoparticles, and were correlated to electrical conductivity measurements. Parameters such as number of particles in contact and junction distance between the nano particles in the composites are suggested as a way of enhancing electrical conductivity.